Who Benefits from Capital Account Liberalization? : Evidence from Firm-Level Credit Ratings Data - Prati, Alessandro (IMF Working Papers; Working Paper ;, 2009)
We provide new firm-level evidence on the effects of capital account liberalization. Based on corporate foreign-currency credit ratings data and a novel capital account restrictions index, we find that capital controls can substantially limit access to, and raise the cost of, foreign currency debt, especially for firms without foreign currency revenues. As an identification strategy, we exploit, via a difference-in-difference approach, within-country variation in firms' access to foreign currency, measured by whether or not a firm belongs to the nontradables sector. Nontradables firms benefit substantially more from capital account liberalization than others, a finding that is robust to a broad range of alternative specifications.